Clinical implications of aberrant neurovascular structures coursing through the submandibular gland - Eaton,Kelsey J.; Smith,Heather F. (PeerJ, 2019)
Background Variation within the submandibular triangle, including variant paths of facial neurovasculature, could increase risk of neurovascular derangement during submandibular gland (SMG) dysfunction, enlargement, interventions, or removal. Methods Frequency of anatomical variants enveloped within or piercing the SMG, including facial artery, vein, or branches of CN VII, were assessed in 70 cadaveric submandibular glands (39M/31F). Results Eighteen of 70 SMGs (25.7%) were pierced by at least one aberrant neurovasculature structure: Facial artery most frequently (n = 13), followed by facial vein (n = 2), inferior labial artery and vein (n = 1), and CN VII cervical branch (n = 1). This study demonstrated the high variability of neurovasculature within submandibular parenchyma. These aberrant neurovascular structures, especially facial artery, are in danger of compromise during surgical and other medical procedures on the SMG. To avoid potential neurovascular compromise, ultrasonographic or other imaging is recommended prior to procedures involving the SMG.
Keywords: Anatomical variation; Facial artery; Salivary glands; Surgery; Otolaryngology